Cytogenetic and epidemiological findings in Down syndrome, England and Wales 1989 to 1993. National Down Syndrome Cytogenetic Register and the Association of Clinical Cytogeneticists. Issue 5 (May 1996) - Mutton, D; Alberman, E; Hook, E B
Abstract : Data from the National Down Syndrome Cytogenetic Register is used to describe the cytogenetics and epidemiology of registered cases. The register comprises notifications from cytogenetics laboratories in England and Wales. This report is of 5737 cases registered between 1989 and 1993: 2169 prenatal and 3436 postnatal diagnoses, and 132 spontaneous abortions. Eighty eight registrations were from multiple pregnancies. Ninety five percent had regular trisomy 21. In 4% there was a translocation, mostly Robertsonian t(14;21) or t(21;21). One percent were mosaics with one normal cell line. Mean maternal age was raised in free trisomy 21, but not in translocations. Where families had been investigated, about a third of translocations were inherited, six to seven times more often from the mother than the father. Associations between free trisomy 21 and structural chromosomal defects in the births were no more common than expected from newborn series. The overall sex ratio was raised (male to female: 1.23 to 1), and there was an excess of associated male sex chromosomal aneuploidy. However, in mosaics with one normal cell line the male to female ratio was 0.8 to 1, and in twins discordant for trisomy 21 there was also a female excess.